ENGLISH STUDENTS’ ACADEMIC-EMOTIONS IN LEARNING SPEAKING AT THE BEGINNING OF ONLINE LEARNING TIME AMID COVID-19 PANDEMIC: A narrative study - Euis Rina Mulyani; Rasi Yugafiati; Karin Nurul Fatia (IKIP Siliwangi, 2021)
Academic emotions are essential factors for students’ successfulness in language learning. The present research was aimed at portraying academic emotions of Indonesian undergraduate students majoring English during transition from face-to-face learning to online one in speaking course due to COVID-19 pandemic. This study used qualitative method, particularly narrative study. The participants were four students majoring English language education of a private university in West Java, Indonesia. They took part in this study voluntarily. To gain the needed data, interviews were conducted. The data, was firstly analysed using Mile and Huberman’s (1994) concept of analysing qualitative data. Further, Hascher’s (2009) types of academic emotions was employed for further data analysis. This study revealed that negative emotions – bored, less motivated, doubtful, sadness, and worry – emerged because there was discrepancy between the students’ conception and the reality regarding what and how learning speaking were. Keywords: Academic Emotions, English-Department Students, Online Learning